A survey of mental health in the workplace : a human resource perspective : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Ripley, Nadine T (Massey University, 1997)
The present study is exploratory in nature, utilising the survey method of research to address the topic of occupational mental health. This theme within the broader topic of occupational health and well-being has not previously been explored through the use of a quantitative or qualitative research method in the New Zealand workplace. A questionnaire was constructed to elicit information and develop an understanding of Human Resource practitioners' perceptions and practice concerning various occupational mental health issues. The sample consisted of 625 randomly selected Human Resource practitioners within the Auckland and Wellington regions of New Zealand. The final number of participants who responded to the survey was 164. The Human Resource practitioners acknowledged that organisations have a responsibility to address mental health issues in the workplace. Psychological/emotional issues were perceived as prevalent. The Human Resource practitioners demonstrated an understanding of the high impact of work and non-work stressors on employee psychological health as well as the negative impact that poor employee mental well-being has on organisational outcomes and individual outcomes. Human Resource practitioners perceived primary interventions to be most commonly implemented, followed by tertiary interventions and secondary interventions. Employee Assistance Programmes were reported to be the most prevalent intervention and were perceived to be effective in addressing mental health in the workplace. The implications of the study include the need for an increased understanding of work-based interventions addressing mental health in the workplace to enable the Human Resource practitioners to make informed contributions to organisations taking responsibility to address occupational mental health.
Keywords: Employees; Industrial psychiatry; Industrial psychology; Mental health